1995
DOI: 10.1111/j.1365-2826.1995.tb00724.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Antidepressant Treatment Reduces Behavioural Deficits in Transgenic Mice with Impaired Glucocorticoid Receptor Function

Abstract: Impaired cognitive function and enhanced activity of the hypothalamic-pituitary-adrenocortical system are among the cardinal symptoms of major depression in humans that resolve after successful antidepressant treatment. We used a transgenic mouse model expressing antisense RNA complementary to that of glucocorticoid receptor (GR) mRNA to test the hypothesis that reduced GR function can cause these clinical disturbances. The transgenic mice show profound behavioural changes in a number of animal tests that are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
101
3

Year Published

1999
1999
2008
2008

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 157 publications
(109 citation statements)
references
References 41 publications
5
101
3
Order By: Relevance
“…This resulted in a mouse expressing GR antisense mainly in neuronal tissue and this mutant was expected to be a well-suited animal model of depression associated with impaired GR function (Pepin et al 1992). This transgenic mouse was extensively studied and the main findings that emerged were the following: 1) these mice needed higher dexamethasone dosages than control mice in order to display corticosterone suppression under basal conditions or following CRH (Stec et al 1994); 2) CRH-elicited ACTH was higher in transgenic mice but corticosterone was lower in comparison to controls ; 3) these mice showed decreased corticosterone response to exogenous ACTH ); 4) when stressed, these mice showed increased ACTH levels, whereas corticosterone levels remain unchanged (Karanth et al 1997); 5) Dijkstra et al (1998) showed reduced activity of CRH neurons in the PVN of these mice and decreased sensitivity of pituitary CRH-R1 mRNA to stimulus-induced desensitisation; 6) these mice displayed an enhanced locomotorstimulating effect to morphine, a response that is reflected by an enhanced dopaminergic activity within the mesolimbic system (Spanagel et al 1996); 7) in these mice, responses to endotoxin were aberrant as noted by Linthorst and coworkers (1999), confirming that immune function is critically determined by appropriate GR function; 8) several studies (e.g., Montkowski et al 1995;Rousse et al 1997;Rochford et al 1997; showed that these mice have impairments in learning and memory paradigms which are also influenced by age; 9) Steckler et al (1999) concluded that allocentric spatial navigation is impaired whereas egocentric navigation is unimpaired. The latter authors suggested that the observed effects were due to hippocampal dysfunction secondary to GR deficiency and possible compensatory changes.…”
Section: Transgenic Mice Expressing Gr Antisensementioning
confidence: 56%
“…This resulted in a mouse expressing GR antisense mainly in neuronal tissue and this mutant was expected to be a well-suited animal model of depression associated with impaired GR function (Pepin et al 1992). This transgenic mouse was extensively studied and the main findings that emerged were the following: 1) these mice needed higher dexamethasone dosages than control mice in order to display corticosterone suppression under basal conditions or following CRH (Stec et al 1994); 2) CRH-elicited ACTH was higher in transgenic mice but corticosterone was lower in comparison to controls ; 3) these mice showed decreased corticosterone response to exogenous ACTH ); 4) when stressed, these mice showed increased ACTH levels, whereas corticosterone levels remain unchanged (Karanth et al 1997); 5) Dijkstra et al (1998) showed reduced activity of CRH neurons in the PVN of these mice and decreased sensitivity of pituitary CRH-R1 mRNA to stimulus-induced desensitisation; 6) these mice displayed an enhanced locomotorstimulating effect to morphine, a response that is reflected by an enhanced dopaminergic activity within the mesolimbic system (Spanagel et al 1996); 7) in these mice, responses to endotoxin were aberrant as noted by Linthorst and coworkers (1999), confirming that immune function is critically determined by appropriate GR function; 8) several studies (e.g., Montkowski et al 1995;Rousse et al 1997;Rochford et al 1997; showed that these mice have impairments in learning and memory paradigms which are also influenced by age; 9) Steckler et al (1999) concluded that allocentric spatial navigation is impaired whereas egocentric navigation is unimpaired. The latter authors suggested that the observed effects were due to hippocampal dysfunction secondary to GR deficiency and possible compensatory changes.…”
Section: Transgenic Mice Expressing Gr Antisensementioning
confidence: 56%
“…at the level of post-receptor signaling cascades (Holsboer 2000), including differences in the homo-or heterodimerization pattern of gluco-and mineralocorticoid receptors (Trapp et al 1994) and their association with transcription factors and chaperones (Truss and Beato 1993). In support of this notion is the previous finding that in transgenic mice with impaired GR function, long-term treatment with the antidepressant moclobemide led to an increased GR function without changes in GR binding (Montkowski et al 1995).…”
Section: Involvement Of Glucocorticoid and Mineralocorticoid Receptorsmentioning
confidence: 89%
“…Mice with decreased glucocorticoid receptor gene expression (by transgenic expression of antisense mRNA directed against the receptor) exhibit reduced hypothalamic CRH expression [20], enhanced stress-associated ACTH response [21][22][23], and impaired efficiency of glucocorticoid-mediated negative feedback [21,[23][24][25]. These mice exhibit deficits in spatial learning, enhanced responses to novelty and decreased locomotion in familiar environments [6].…”
Section: Modulation By Mineralocorticoid and Glucocorticoid Receptorsmentioning
confidence: 99%